I-Vague Vector Spaces - Zelalem Teshome Wale ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2020)
The notions of I-vague vector spaces of vector spaces with membership and non-membership functions taking values in an involutary dually residuated lattice ordered semigroup are introduced which generalizes the notions with truth values in a Boolean algebra as well as those usual vague sets whose membership and non-membership functions taking values in the unit interval [0, 1]. We discuss some properties of I-vague vector spaces.